2016
DOI: 10.1539/joh.15-0100-fs
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal symptoms among garment workers in Kandal province, Cambodia

Abstract: Prevalence of musculoskeletal symptoms among garment workers in Kandal province, Cambodia: Leap Van, et al. Department of Community Medicine, Faculty of Medicine, Khon Kaen University, Thailand Objective The main objectives of this cross‐sectional descriptive study were to identify the prevalence of musculoskeletal symptoms and workstation biomechanical risk levels for garment workers in Kandal Province, Cambodia. Methods This cross‐sectional descriptive study used multistage sampling techniques to select 714 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
(36 reference statements)
2
14
0
5
Order By: Relevance
“…One common symptom that arises from work is musculoskeletal disorders. Musculoskeletal Disorder is a health problem involving the joints, muscles, tendons, skeleton, cartilage, ligaments, and nerves (Van et al, 2016). Musculoskeletal Disorder is related to the intensity and severity of work, although often light activities such as housework or exercise may also be involved (Barro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One common symptom that arises from work is musculoskeletal disorders. Musculoskeletal Disorder is a health problem involving the joints, muscles, tendons, skeleton, cartilage, ligaments, and nerves (Van et al, 2016). Musculoskeletal Disorder is related to the intensity and severity of work, although often light activities such as housework or exercise may also be involved (Barro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have showed the presence of ergonomic hazards both in the textile and garment department that could increase the risk of MSDs (27)(28)(29). Also, ergonomic hazard exposure assessment studies in Bangladesh and Cambodia found that the tasks in garment production gave high risk of MSDs (10,12). It is likely that the development of MSDs may be linked to exposure to ergonomic hazards in the textile and garment departments.…”
Section: Work-related Factorsmentioning
confidence: 99%
“…However, the work processes in textile and garment production expose workers not only to dust but also to other different hazards (8,9). For instance, the presence of heavy machines and mechanical contact, manual handling, repetitive work and work in awkward postures as well as increased work pressure can put workers at risk for work-related diseases, such as musculoskeletal disorders (MSDs) and traumatic injuries (10)(11)(12). In the past years, studies have described various health problems among workers in the textile and garment sector (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal Disorder adalah masalah kesehatan yang melibatkan sendi, otot, tendon, kerangka, tulang rawan, ligamen, dan saraf (Van 2016). Tingkat musculoskeletal disorder dari yang paling ringan hingga yang berat akan menggangu konsentrasi dalam bekerja, menimbulkan kelelahan dan pada akhirnya akan menurunkan produktivitas (Harcombe 2014).…”
Section: Pendahuluanunclassified